Analisis Yuridis Terhadap Praktik Jual Beli Surat Keterangan Sakit Tanpa Validasi Dokter Melalui E-Commerce - Kadek Diah Indrayani; I Nyoman Putu Budiartha; Ida Bagus Gede Agustya Mahaputra (Warmadewa Press, 2024)
The development of E-Commerce in Indonesia lately is very rapid where people tend to use E-Commerce to fulfill their needs, including the services of making important documents. The problems that arise are: How is the Legality of Buying and Selling Sick Certificates Without Doctor Validation Through E-Commerce? And what are the Legal Consequences of the Seller of Sick Certificate through E-Commerce? This research uses normative legal research. The legality of buying and selling sick certificates without doctor validation through e-commerce is regulated in Article 35 of Law Number 29 of 2004 concerning Medical Practices, Article 7 of KODEKI, and Article 28 of Law Number 11 of 2008 concerning Information and Electronic Transactions. The legality of a sick certificate will only be valid if it is issued by a doctor who has a registration certificate with the validity of the results of his own examination. So the letter circulating in E-Commerce is a fake sick certificate because it is not a doctor or medical personnel who issued it, and can be punished in accordance with the articles on the ITE Law and the article on forgery of letters.